2014
DOI: 10.1542/peds.2013-4147
|View full text |Cite
|
Sign up to set email alerts
|

The Transition to ICD-10-CM: Challenges for Pediatric Practice

Abstract: BACKGROUND AND OBJECTIVES: Diagnostic codes are used widely within health care for billing, quality assessment, and to measure clinical outcomes. The US health care system will transition to the International Classification of Diseases, 10th Revision, Clinical Modification (ICD-10-CM), in October 2015. Little is known about how this transition will affect pediatric practices. The objective of this study was to examine how the transition to ICD-10-CM may result in ambiguity of clinical informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…6 In contrast, family medicine mapping is slightly more complex than oncology with a convolution rate of 18%. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In contrast, family medicine mapping is slightly more complex than oncology with a convolution rate of 18%. 4 …”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies have evaluated a number of different medical specialties in regards to the transition to ICD-10-CM. 46 The recent ruling by Center for Medicaid and Medicare Services to not deny any claim due to lack of specificity for the first year during the transition to ICD-10-CM highlights the challenge and potential impact of the new coding system. 7 To our knowledge, no other studies have evaluated the impact ICD-10-CM will have on the practice of family medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments are not alone in facing ICD-10-CM transition challenges. Prior studies indicated significant percentage of convoluted code mappings and information loss due to clinically incorrect mappings in evaluation of hematology-oncology [11] and pediatrics [12] patient accounting data. Because ICD codes are utilized for adverse effects reporting by hospitals, Patient Safety Indicators (PSI) compiled by the Agency for Healthcare Research and Quality (AHRQ) might suffer from similar challenges [13].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was simpler after the initial transcription of the records, just tabulation of missing data and comparison of the registers counts with the monthly reports. The simplified version of the data quality assessment is counting from the summary tables, the proportion of reporting health facilities and the total reports submitted against the expected [12][13][14][15][16]. However, these methods leave out the recording process, which is an essential step toward quality assessment.…”
Section: Data Analysis Presentation and Finding Disseminationmentioning
confidence: 99%